Juridical analysis of personal data protection in the case of BPJS personal data leakage reviewed from a positive legal perspective - Everdina Cathrine Tesaldnika Pattipeilohy (Trigin Publisher, 2023)
The progress of the Internet today is very rapid, if you need and search for information can be done with the help of modern technology. The basic principle of personal data protection is the principle of restriction of data use which confirms that personal data must not be disclosed, provided or used for purposes other than those prescribed, except with the consent of the data owner or by legal authorities. In addition, there are also Data Protection Principles that emphasize the importance of protecting personal data by maintaining reasonable security against risks such as loss, access, destruction, use, modification, or unauthorized disclosure of data. The case of leakage of BPJS personal data is the responsibility of the BPJS institution (government) as an Electronic System Operator supported by Article 47 of the Personal Data Protection Law. BPJS as a public institution that is an electronic system operator must ensure that in managing personal data must be in accordance with the principles of personal data protection in accordance with the new PDP Law and ensure that even though it cooperates with third parties, it is monitored as well and as much as possible so as not to become a data leak again.